2006
DOI: 10.1063/1.2203956
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly from the branch pattern to parallel wire array in electrodeposition

Abstract: We report a self-organized copper electrodeposition without imposed templates and induced additives. The deposit morphology on the silicon substrate varies from a branch to a parallel pattern by changing the applied voltage. We suggest that there are two essential factors for the formation of such kind of copper wire arrays. One is a proper electric potential distribution near the tip of the copper wire which dictates the direction of the solute transport. The other one is that the cathode overpotential and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…9). The broadening of the PO 4 3− adsorption bands observed after 15 min of deposition suggests that in this case the coating was constituted by a not organized HA. The adsorption bands become sharper as the crystals grow.…”
Section: Coating Growthmentioning
confidence: 87%
See 4 more Smart Citations
“…9). The broadening of the PO 4 3− adsorption bands observed after 15 min of deposition suggests that in this case the coating was constituted by a not organized HA. The adsorption bands become sharper as the crystals grow.…”
Section: Coating Growthmentioning
confidence: 87%
“…Zhang et al [4] have analyzed the growth of cooper nano-wires by electrodeposition on silicon substrates. They have shown that an equipotential distribution of lines near Cu-wire tips reaches a critical value and therefore optimum deposition conditions can be defined at certain voltage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations